1969
DOI: 10.1002/pssb.19690350213
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Conductivity of Single Crystalline Nickel Oxide

Abstract: The electrical conductivity of single crystalline NiO was found to be proportional to the 1/4 power of the oxygen pressure for oxygen partial pressures between loo and 10-4 atm over the temperature range of 900 to 1200 "C. These results are in agreement with singly ionized cation vacancies as the predominant nonstoichiometric defect. The sum of the enthalpies of formation of nonstoichiometric disorder and activated enthalpy of movement of an electron hole was found to remain constant when thermodynamic equilib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

1970
1970
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 39 publications
0
14
0
1
Order By: Relevance
“…Transition-metal oxides (particularly cobalt, nickel, and manganese oxides) are one of the most promising alternative catalysts because of their abundant reserves and strong corrosion resistances. Among them, porous nickel oxides (NiO x ) nanosheets are considered the most suitable alternatives owning to high superior catalytic activities, safety, low cost, and easy preparation . However, the inherent low electronic conductivities, poor ion transport kinetics, and cycling durability of nickel oxides restrict their extensive use. , Recently, material design strategies demonstrated that the electrocatalytic activities of NiO x -based electrocatalysts can be efficiently increased by increasing the conductivity or inducing more active sites, e.g., by designing nanostructured NiO (nanoflakes or nanosheets), introducing foreign dopants (Fe-doped NiO) or constructing heterostructures to accelerate the electron transfer (Co 3 O 4 @NiO, Ni@NiO). Among them, N doping has been widely used to improve the catalytic activities of the electrocatalysts since the electron-donor activities (N-doped Ni 2 P 4 O 12 ) or more available active surface area (N-doped Co 3 O 4 nanosheets, N-doped MoS 2 , or MoSe 2 nanosheets). , In addition, porosity engineering is also an effective strategy to develop high-efficiency electrocatalysts, which can expose and utilize more active sites and provide continuous charge transport pathways. , …”
Section: Introductionmentioning
confidence: 99%
“…Transition-metal oxides (particularly cobalt, nickel, and manganese oxides) are one of the most promising alternative catalysts because of their abundant reserves and strong corrosion resistances. Among them, porous nickel oxides (NiO x ) nanosheets are considered the most suitable alternatives owning to high superior catalytic activities, safety, low cost, and easy preparation . However, the inherent low electronic conductivities, poor ion transport kinetics, and cycling durability of nickel oxides restrict their extensive use. , Recently, material design strategies demonstrated that the electrocatalytic activities of NiO x -based electrocatalysts can be efficiently increased by increasing the conductivity or inducing more active sites, e.g., by designing nanostructured NiO (nanoflakes or nanosheets), introducing foreign dopants (Fe-doped NiO) or constructing heterostructures to accelerate the electron transfer (Co 3 O 4 @NiO, Ni@NiO). Among them, N doping has been widely used to improve the catalytic activities of the electrocatalysts since the electron-donor activities (N-doped Ni 2 P 4 O 12 ) or more available active surface area (N-doped Co 3 O 4 nanosheets, N-doped MoS 2 , or MoSe 2 nanosheets). , In addition, porosity engineering is also an effective strategy to develop high-efficiency electrocatalysts, which can expose and utilize more active sites and provide continuous charge transport pathways. , …”
Section: Introductionmentioning
confidence: 99%
“…Many authors obtained the value of the exponent 1=n s close to~1/6 [12,16,17,38]. In most works, higher values were obtained (1/5), also close to 1/4 [10,11,22,23,25]. Using the above fact as a basis, it is assumed that in Ni 1Àd O, single ionized vacancies are also present.…”
Section: Introductionmentioning
confidence: 89%
“…Similar approaches can be applied to nonstoichiometric compounds with cation vacancies (Cu 2-d O-type oxide), oxygen interstitials (UO 2 þ d -type oxide), and so on [80,[82][83][84][85][86].…”
Section: D11 Real Oxide Structuresmentioning
confidence: 99%